2015
DOI: 10.1097/mao.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study of U.S. Children Unable to Achieve Open-Set Speech Recognition 5 Years After Cochlear Implantation

Abstract: Objective To identify characteristics associated with inability to progress to open-set speech recognition in children who are 5 years post cochlear implantation. Study Design Prospective, longitudinal and multidimensional assessment of auditory development over 5 years. Setting Six tertiary cochlear implant (CI) referral centers in the US. Patients Children with severe-to-profound hearing loss who underwent implantation before age 5 years enrolled in the Childhood Development after Cochlear Implant (CDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
(47 reference statements)
1
20
0
5
Order By: Relevance
“…(39,40) For example, the 1-year data in the present study indicate lower scores on the IT-MAIS/MAIS and ESP than the 1-year post CI mean scores for 42 pairs (CI and normally hearing) of children assessed in the national Childhood Development after Cochlear Implantation (CDaCI) study. (41) Young(32) reported that in some cases of CI in cochlear nerve deficiency, development of adequate responses may take several years.…”
Section: Discussionmentioning
confidence: 70%
“…(39,40) For example, the 1-year data in the present study indicate lower scores on the IT-MAIS/MAIS and ESP than the 1-year post CI mean scores for 42 pairs (CI and normally hearing) of children assessed in the national Childhood Development after Cochlear Implantation (CDaCI) study. (41) Young(32) reported that in some cases of CI in cochlear nerve deficiency, development of adequate responses may take several years.…”
Section: Discussionmentioning
confidence: 70%
“…Auditory and speech-perception outcomes. Speech perception was assessed once before surgery and again at 6 mo postactivation using the Speech Recognition Index in Quiet (SRI-Q) (29), following previous longitudinal CI studies (8,23,30). The SRI-Q consisted of a hierarchy of measures of speech-recognition abilities (see Materials and Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…For example, greater maternal sensitivity to communication needs of the child predicts better speech recognition performance (87); interpersonal family dynamics have not been explored at all in adult CI users. Similarly, the role of intensive postoperative aural rehabilitation has been emphasized in the pediatric population but has primarily been limited in adult CI users to patient-driven computerized auditory training (88).…”
Section: Introductionmentioning
confidence: 99%